IMC Based PID Control of a Magnetic Levitation System. (2016) - Duka, Adrian-Vasile; Dulău, Mircea; Oltean, Stelian-Emilian
Abstract: Attraction type magnetic levitation devices are nonlinear and unstable systems with fast dynamics. If a model of such a system can be produced, it could be used in the design process of a stabilizing controller. Internal Model Control (IMC) provides a strategy that explicitly uses an existing model of the controlled process for developing a suitable controller. In this paper, a linear model that represents the nonlinear dynamics of the magnetic levitation system is first derived. Then, this model is used in the design procedure of an IMC-based PID controller, which is used for achieving stable levitation of a ferromagnetic object at predetermined distances with the help of the magnetic field produced by a coil. The results are shown by means of digital simulation, based on Simulink.